Fostering Creative Thinking and Creative Products through the STREAM Approach - Utami, Amaira; Sandi, Anggun Pastika; Lutfa, Asna (Jurnal Inovasi Pendidikan IPA, 2025)
With the advancement of science and technology, teaching and learning practices should provide students with information acquisition skills to meet future science, technology, engineering, and mathematics (STEM)-driven labor needs. The integration of arts and religion in STEM education is approved as a primary force in fostering students' 21st-century skills. Creativity is the key component of 21st-century skills measured by creative thinking and product. There is a gap in understanding how integrating religion and arts into STEM study enhances students' creative thinking and creative products. The pre-experiment method is implemented with a one-group pre-test and post-test involving 12 semester four students of the Primary Education Teacher Training Program, University of Nahdlatul Ulama Indonesia. This research implements two instruments: (1) creative thinking test items with fluency, flexibility, originality, elaboration, and evaluation aspects; (2) creative product scoring rubric in human movement system topic in creating robotic hand. The finding shows that the students' creative thinking enhanced quite significantly in all aspects. Specifically, flexibility and elaboration were the two highest creative thinking aspects, proved by a significant enhancement in those two aspects. Moreover, the result of the creative product revealed an average score of 82.44, which was categorized as good. All in all, lecturing with the STREAM approach in creating robotic hands can foster the creative thinking and creative products of the students